A discrete choice experiment on price and flavour effects on the appeal of nicotine products: a pilot study among young adults in Switzerland (Swiss Medical Weekly, 2023)
AIMS: To explore the effects of prices and flavour availability on the appeal of different tobacco and nicotine products, including conventional cigarettes, Electronic Nicotine Delivery Systems (ENDS) and Heated Tobacco Systems (HTS) among an adult population in Switzerland.METHODS: We performed a Discrete Choice Experiment among a group of Swiss aged ≥18 years via the online recruiting platform Prolific in a convenience sample. Our sample included both non-smokers and smokers. We used a within-subject, alternative-specific block design in a series of choice sets including different smoking products. We fixed the attributes of nicotine content (high or medium) and harmfulness (in years of life lost) for each product. Attributes of interest included price (ranging from CHF 5 to 25 in increments of 5) and flavour (fruity/menthol vs none/tobacco flavour). We performed a conditional logistic regression on the attributes’ influence on the appeal of cigarettes, ENDS and HTS.RESULTS: A total of 108 out of 153 participants (n = 25 smokers and n = 83 non-smokers, completion rate = 71%) successfully completed our pilot survey experiment. We found that, in general, increasing the price of combustible cigarettes, ENDS and HTS by one standard deviation (around CHF 7) reduced their appeal by approximately 66% (relative risk [RR]: 0.34; 95% CI: 0.28–0.42). Unflavoured alternative nicotine products were found to be less appealing than flavoured products, especially for non-smokers, with a 86% decrease in appeal (RR: 0.14; 95% CI: 0.13–0.16). For non-smokers, an increase in price by one standard deviation was associated with a decrease in the appeal of any product by approximately 19% (RR: 0.81; 95% CI: 0.72–0.92). For smokers, the effect sizes were smaller, but overall, the appeal of all products decreased with increasing prices and reduced flavours.CONCLUSIONS: Our Discrete Choice Experiment suggests that, for the Swiss context, limiting the availability of flavours for alternative smoking products has the potential to reduce their appeal to non-smokers by 86% and that a small but significant increase in prices to CHF 15 for cigarettes, ENDS and HTS could lead to a major (around 66%) decrease in their appeal.